Jersey Production Quality Control Using Six Sigma and FMEA Methods To Minimize Product Defects - Jasmine, Indy Aurelia; Salma, Sheila Amalia; Susanto, Hadi (JTI: Jurnal Teknik Industri, 2024)
CV. Genethics is a company engaged in the field of clothing with a primary focus on product quality and customer satisfaction. Based on production data for September 2022 to September 2023, defective products were still found in the jersey production process, with the percentage of defects exceeding the company's tolerance limit of 2%. The defects often occur include white spots, wrinkles, ink buildup, faded ink, non-uniform color, and shadow lines. This research aims to identify the causes of defects in the production process, find the root of the problem, and provide improvement recommendations to reduce the percentage of defects so that it approaches the tolerance limit set by the company. The research uses Six Sigma and Failure Mode and Effect Analysis (FMEA) methods to analyze the problem. The main factors that cause defects are people, information, and methods. Based on the FMEA analysis, it was found that the cause of failure with the highest RPN value was the absence of written information regarding standard work procedures, which could potentially cause various types of defects. The proposed solution is to design a new Standard Operating Procedure (SOP) supported by additional documentation. This recommendation is expected to reduce the defect rate and improve quality control in the jersey production process. Keywords: Quality, Defects, FMEA, Six Sigma, Jersey Products